Critical amount of corrosion and failure behavior of flexural reinforced concrete beams. (8th February 2021) - Hansapinyo, Chayanon; Vimonsatit, Vanissorn; Matsushima, Manabu; Limkatanyu, Suchart
Highlights: Corrosion in tension bars more than 30% decreases the ultimate load and ductility. Failure mode of RC beams can be altered from tensile steel yielding to rupture. The critical amount of corrosion that altered the failure mode is 15%. Lower and upper limits of the critical amount of corrosion are 8–25%. Abstract: Offshore structures are subjected to chloride ion penetration leading to corrosion of the embedded steel rebars. A tensile steel bar with non-uniform corrosion such as pitting can rupture prior to yielding. In this study, the critical corrosion amount that causes tensile steel rupture in reinforced concrete beams was determined in two parts of work. In the first part, the flexural performance of low-to-highly corroded reinforced concrete beam was investigated. A series of load tests comprising of 44 reinforced concrete specimens, all having a rectangular section, 80 mm wide by 120 mm deep, and the length of 550 mm, were conducted. Each beam was reinforced with one D10 steel bar as the tension reinforcement, one acrylic top reinforcement and sufficient shear reinforcement to avoid shear failure mode. The corrosion in the steel bars was induced with an electrolytic set up with the controlled amount based on Faraday's law. These bars were extracted from the beams to measure the actual corrosion amount after the test. The results show a sharp reduction in the ultimate load and ductility when the corrosion was over 30%, and concrete crushing was observed at failure. In the second part of the work, tension tests of 17 D10 bars with 0–15% corrosions were carried out to investigate the rupture strain of the bars. The test results show the exponential decay function of the rupture strain as the corrosion increases. The obtained decay function was then used in determining the bending capacity and the failure mode of RC beams. Based on the calculation, the critical amount of corrosion altering the failure mode from yielding to rupture was 15%. Moreover, to reflect uncertainties in the natural process of the corrosion, the variation of the corrosion amount due to the pitting behavior and the rupture strain with the obtained standard deviations of the test data were considered. Accordingly, the lower and upper limits of the critical amount of corrosion were 8–25%, respectively.